2013
DOI: 10.1111/scs.12064
|View full text |Cite
|
Sign up to set email alerts
|

Gerontological nurses' perceptions of their rights in Finland

Abstract: On the basis of our findings, especially in very demanding areas of nursing, like older people care, nurses' rights deserve major visibility and should be taken into consideration when planning care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Meanwhile, Carter ( 2014 ) stated that nurses who had a calling displayed ‘a passive docility or strict obedience’, which questioned their freedom and self‐determination. The increased attention paid to nurses' working conditions (McDermid et al, 2020 ) and rights (Kangasniemi et al, 2014 ) has increased nurses' awareness of them and could have made it easier for them to speak out. The negative consequences that nurses linked to calling could explain why the nurses in our study were less likely to have a calling than the other groups of professionals who took part.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Carter ( 2014 ) stated that nurses who had a calling displayed ‘a passive docility or strict obedience’, which questioned their freedom and self‐determination. The increased attention paid to nurses' working conditions (McDermid et al, 2020 ) and rights (Kangasniemi et al, 2014 ) has increased nurses' awareness of them and could have made it easier for them to speak out. The negative consequences that nurses linked to calling could explain why the nurses in our study were less likely to have a calling than the other groups of professionals who took part.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was legally approved in the United States in 1995, allowing nurses to refuse certain assignments for which they do not have the required competence, abilities, skills, or training [49]. Based on our literature review, while we found many examples of disrespect for nurses as well as physical or psychological harm [38,40,42,[50], [51], [52], [53], [54]], there was no evidence of support for a theme related to nurses’ rights as a dimension of professional autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in addition to providing care and support to patients, nurses were exposed to a wide range of unrelated assignments. A clear framework for nursing duties and responsibilities is an essential part of the nursing profession, used as a guideline to provide better nursing quality and care to patients [19,54]. A study conducted in Turkey concluded that nursing activity performed within the framework of a clear job description and the withholding of unrelated assignments (secretarial activities, managing laboratory results) were essential to enhance the professional autonomy of nurses [12].…”
Section: Discussionmentioning
confidence: 99%